2009
DOI: 10.1016/j.bpj.2009.03.014
|View full text |Cite
|
Sign up to set email alerts
|

An Alpha-Helical Peptide in AOT Micelles Prefers to be Localized at the Water/Headgroup Interface

Abstract: A model alpha-helical peptide encapsulated in a reverse micelle is used to study the structure and dynamics of proteins under constrained environments that mimic the membrane-water environment in cells. Molecular dynamics simulations of the self assembly of systems composed of a peptide, sodium bis(2-ethylhexyl) sulfosuccinate (AOT), water, and isooctane show that the peptide prefers to be located at the water/AOT headgroups interface. We explore the effect of the AOT headgroup charge and the peptide charge an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 26 publications
2
18
0
Order By: Relevance
“…After encapsulation by the RM, the helical peptide remained at the water/AOT/isooctane interface such that the peptide and AOT head groups shared coordinated water molecules, and the entropy loss of the water is reduced. 46 Our study employs MD calculations to simulate systems approximating those examined by Gai and co-workers, with a focus on elucidating the structure and dynamics of the AOT RM with and without peptide. Our goal is to acquire an atomic-level understanding of the effect that the RM environment (w 0 = 6) has on the conformational folding equilibrium of the alanine-based peptide, AKA 2 (ACE-YGAKAAAA-(KAAAA) n G-NH 2 where n = 2).…”
Section: B the Nature Of A Reverse Micelle Environment In Peptide Comentioning
confidence: 99%
“…After encapsulation by the RM, the helical peptide remained at the water/AOT/isooctane interface such that the peptide and AOT head groups shared coordinated water molecules, and the entropy loss of the water is reduced. 46 Our study employs MD calculations to simulate systems approximating those examined by Gai and co-workers, with a focus on elucidating the structure and dynamics of the AOT RM with and without peptide. Our goal is to acquire an atomic-level understanding of the effect that the RM environment (w 0 = 6) has on the conformational folding equilibrium of the alanine-based peptide, AKA 2 (ACE-YGAKAAAA-(KAAAA) n G-NH 2 where n = 2).…”
Section: B the Nature Of A Reverse Micelle Environment In Peptide Comentioning
confidence: 99%
“…However, there are also weaker entropic forces associated with the surfactant and the protein hydration that provide a driving force for binding of the protein to the RM surface. Previous calculations 26 and experiments 14,17 on charged and neutral alpha helical peptides have shown that the peptides have a preference for the RM interface.…”
Section: Discussionmentioning
confidence: 97%
“…29 Experiments in RM are conducted with different solvents. 14,17,18 However, to maintain consistency in the force field and with previous simulations, 26,29,32,33 we use iso-octane as the organic solvent. Simulations are conducted with the parallel molecular dynamics program NAMD.…”
Section: A Simulations Of Ubiquitin-aot Rm Self Assemblymentioning
confidence: 99%
See 2 more Smart Citations